Global Nutrition Report 2015: Actions and accountability to advance nutrition and sustainable development - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
As we move into the post-2015 era of the Sustainable Development Goals (SDGs), the world faces many seemingly intractable problems. Malnutrition should not be one of them. Countries that are determined to make rapid advances in malnutrition reduction can do so. If governments want to achieve the SDG target of ending all forms of malnutrition by 2030, they have clear pathways to follow. There are many levers to pull, and this report provides many examples of countries that have done so. Tackling malnutrition effectively is also key to meeting many other SDG targets. Good nutrition signals the realization of people’s rights to food and health. It reflects a narrowing of the inequalities in our world. Without good nutrition, human beings cannot achieve their full potential. When people’s nutrition status improves, it helps break the intergenerational cycle of poverty, generates broad-based economic growth, and leads to a host of benefits for individuals, families, communities, and countries. Good nutrition provides both a foundation for human development and the scaffolding needed to ensure it reaches its full potential. Good nutrition, in short, is an essential driver of sustainable development.